The Influence of Digital Leadership, Technology Use, and Culture on Employee Performance - Wijaya , Ardiansyah Hadi; Subroto , Setyowati; Amalia , Mei Rani (Jurnal Economic Resource, 2025)
This study examines the influence of digital leadership transformation, digital technology utilization, and organizational culture on employee performance at PT. Plambo Pratama Joyosantoso Pemalang. Using a quantitative approach with 75 respondents, data were analyzed through multiple linear regression. Results show that digital leadership (sig. 0.000), technology utilization (sig. 0.000), and organizational culture (sig. 0.002) significantly affect performance. Simultaneously, all three variables have a significant effect (F = 289.266, sig. 0.000). In conclusion, digital transformation in leadership, technology, and culture positively impacts employee performance